2015
DOI: 10.3892/mmr.2015.4517
|View full text |Cite
|
Sign up to set email alerts
|

Sequential changes in autophagy in diabetic cardiac fibrosis

Abstract: Abstract. Autophagy is considered to be associated with cardiac fibrosis. However, whether autophagy accelerates or ameliorates fibrosis remains to be elucidated. In the present study, 36 rats were divided into two groups: Control rats and diabetic rats. The diabetic rats were established by feeding the animals a high fat diet combined with streptozotocin. From the two groups, six rats were sacrificed after 1, 6 and 7 months. Cardiac systolic functions were measured. The collagen volume fraction was calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
3
8
0
Order By: Relevance
“…Fasudil inhibited the induction of ROCK1 and ROCK2 mRNA levels. This finding is consistent with previous studies that reported activation of ROCK by high glucose and inhibition of ROCK by fasudil . Thus, the data indicate that fasudil inhibits ROCK by decreasing its expression.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Fasudil inhibited the induction of ROCK1 and ROCK2 mRNA levels. This finding is consistent with previous studies that reported activation of ROCK by high glucose and inhibition of ROCK by fasudil . Thus, the data indicate that fasudil inhibits ROCK by decreasing its expression.…”
Section: Discussionsupporting
confidence: 93%
“…In response to malnutrition, autophagosomes chelate reactive oxygen species (ROS)‐generating mitochondria to protect cells, while 3‐MA increases the production of ROS and advances apoptosis . Our previous study demonstrated that autophagy‐related protein expression was increased in diabetic rat hearts . Interestingly, in the current study, 3‐MA reversed fasudil's effects on cell proliferation and apoptosis.…”
Section: Discussionsupporting
confidence: 41%
See 2 more Smart Citations
“…We observed a significant increase of LC3-I in EAT which may indicate that EAT has more capacity for macroautophagy than SAT. Moreover, the levels of LC3-II in EAT were also significantly increased, and together with the increase of Beclin 1 and P-AMPK, these results are suggestive of an increased autophagy in EAT compared to SAT, in agreement with previous studies [101-103]. As mentioned before, EAT exhibits increased ER stress and, as such, increase in misfolded or dysfunctional proteins.…”
Section: Discussionsupporting
confidence: 91%